2015
DOI: 10.3928/1081597x-20150521-08
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront-Guided Laser Treatment Using a High-Resolution Aberrometer to Measure Irregular Corneas: A Pilot Study

Abstract: Wavefront-guided laser enhancements using the evaluated platform seem to be safe and effective to restore the visual function in aberrated eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
4
14
2
Order By: Relevance
“…The significant visual improvement obtained in our series was due to the reduction of the spherocylindrical error and the minimization of HOAs. Specifically, the SE was reduced from a mean preoperative value of 23.22 6 1.32 D to a mean postoperative value of 20.68 6 0.64 D at the last follow-up visit, with 62% of the cases having an SE within 60.50 D. This outcome is consistent with that obtained in our previous pilot study, 12 as well as in other studies evaluating the sequential and simultaneous CXL + WFG PRK approaches in keratoconus. 17,19,28,29 In contrast, Kanellopoulos 20 found in the comparative study of sequential versus simultaneous CXL + PRK in keratoconus, more reduction in the SE refraction with the simultaneous treatment (2.50 6 1.20 vs. 3.20 6 1.40 D).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The significant visual improvement obtained in our series was due to the reduction of the spherocylindrical error and the minimization of HOAs. Specifically, the SE was reduced from a mean preoperative value of 23.22 6 1.32 D to a mean postoperative value of 20.68 6 0.64 D at the last follow-up visit, with 62% of the cases having an SE within 60.50 D. This outcome is consistent with that obtained in our previous pilot study, 12 as well as in other studies evaluating the sequential and simultaneous CXL + WFG PRK approaches in keratoconus. 17,19,28,29 In contrast, Kanellopoulos 20 found in the comparative study of sequential versus simultaneous CXL + PRK in keratoconus, more reduction in the SE refraction with the simultaneous treatment (2.50 6 1.20 vs. 3.20 6 1.40 D).…”
Section: Discussionsupporting
confidence: 90%
“…This result is consistent with that obtained in our previous pilot study in which a significant reduction in trefoil RMS was also found. 12 Likewise, Shetty and et al 34 also found a reduction in some corneal HOAs after simultaneous CXL and topography-guided PRK, the change being only statistically significant for the trefoil and spherical aberration and of less magnitude than that found in our series for ocular aberrations. Alessio et al 31 found that the total and coma-like aberrations were not decreased significantly for all pupil diameters after simultaneous CXL and topography-guided PRK in keratoconus.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Specifically, these advances have allowed surgeons to overcome some limitations concerning the characterization of ocular aberrations and therefore to obtain improved outcomes using wavefront-guided (WFG) ablation profiles, even in the more complex cases 2,46. There is a variety of studies confirming the safety and efficacy of WFG laser in situ keratomileusis (LASIK) for the correction of spherocylindrical refractive errors with the latest laser platforms as well as the ability of these treatments to minimize the induction of higher order aberrations (HOAs) and reduce the level of some preexisting HOAs 13,515…”
Section: Introductionmentioning
confidence: 99%